Unveiling hydro-edaphic dynamics of the Manakudy Estuary: implications for ecosystem health - Adyasha Sahu; N. Jayakumar; C. Sudhan; R. Durairaja; P. Padmavathy; P. Velmurugan; Debabrata Panda; Kamei Ringjonmeilu; Sanjay Chandravanshi; Narsingh Kashyap (Journal of Fisheries, 2026)
The present study investigated the seasonal variations of physicochemical and sediment parameters in the Manakudy Estuary, a critical tropical estuarine ecosystem in India. Key water quality variables encompassing basic physicochemical properties, oxygen dynamics, inorganic carbon, major ions, primary productivity, and nutrient regimes were analysed, as these collectively regulate estuarine biogeochemical processes and biological functioning. These parameters are essential as they collectively influence the chemical and biological environment of the estuary. Seasonal samples were collected from three selected sites across the estuary over a one-year period from March 2024 to February 2025, covering four seasons with triplicate sampling at each site. Descriptive statistics i.e., mean ± standard error (SE) were calculated based on replicate samples at each site and season to evaluate spatial and temporal variability. Two-way ANOVA revealed significant effects of season and site on several physicochemical and soil parameters (p<0.001), indicating pronounced spatio-temporal heterogeneity in the ecological conditions of the Manakudy Estuary. Such variability reflects shifts in nutrient availability, oxygen balance, and productivity patterns, providing clear insights into the ecological condition and ecosystem health of the Manakudy Estuary and its vulnerability to environmental stressors.